“Even We Are Confused”: A Thematic Analysis of Professionals' Perceptions of Processed Foods and Challenges for Communication - Sadler, Christina R.; Grassby, Terri; Hart, Kathryn; Raats, Monique M.; Sokolović, Milka; Timotijevic, Lada (Frontiers in Nutrition, 2022)
Processed foods are increasingly under the spotlight since the development of classification systems based on proxies for food processing. Published critical reviews and commentaries suggest different views among professional disciplines about the definition and classification of processed food. There is a need to further understand perspectives of professionals on the conceptualisation of processed food and the agreements and disagreements among experts, to encourage interdisciplinary dialogue and aid communication to the public. The aim of this research was to elicit views and understandings of professionals on processed food, their perceptions of lay people’s perceptions of the same, and their perspectives on the challenges of communicating about processed foods to the public. The online discussion groups brought together a range of professionals (n = 27), covering the fields of nutrition, food technology, policy making, industry, and civil society, mixed in 5 heterogenous groups. Through thematic analysis the following themes relating to the conceptualisation of processed food and challenges for communication were identified: 1) Broad concepts that need differentiation; 2) Disagreements on scope and degree of processing; 3) The role of food processing within the food system: the challenges in framing risks and benefits; and 4) The challenge of different perspectives and interests for risk communication. Throughout the discussions blurred lines in the characterisation of processing, processed foods, and unhealthy foods were observed. Participants agreed that consensus is important, but difficult. Participants identified a need for further interdisciplinary dialogue, including public engagement, to break down the observed issues, and work towards a mutual understanding and clear communication messages.